Competency-based assessment tools for regional anaesthesia: a narrative review. (February 2018) - Chuan, A.; Wan, A.S.; Royse, C.F.; Forrest, K.
Abstract: Competency-based assessment tools are used in regional anaesthesia to measure the performance of study participants, trainees, and consultants. This narrative review was performed to appraise currently published assessment tools for regional anaesthesia. A literature search found 397 citations of which 28 peer-reviewed studies met the inclusion criteria of primary psychometric evaluation of assessment tools for regional anaesthesia. The included studies were diverse in the type of assessment and the skill set being assessed. The types of assessments included multiple-choice questions, hand-motion analysis, cumulative sum, visuospatial and psychomotor screening, checklists, and global rating scales. The skill sets that were assessed included holistic regional anaesthesia technical and non-technical performance observed at the bedside, to isolated part-tasks, such as needle tip visualisation under ultrasound. To evaluate validity and reliability, we compared the studies against published medical education consensus statements on ideal assessment tools. We discuss the relative merits of different tools when used to assess regional anaesthesia, the importance of psychometrically robust assessment tools in competency-based anaesthesia education, and directions for future education research in regional anaesthesia.